2019
DOI: 10.1002/ajh.25580
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic contribution of targeted NGS in patients with triple‐negative myeloproliferative neoplasms

Abstract: in Stockholm, Sweden. 2. Cappellini MD, Porter JB, Viprakasit V, Taher AT. A paradigm shift on beta-thalassemia treatment: how will we manage this old disease with new therapies? Blood Rev. 2018;32(4):300-311. 3. Abetz L, Baladi JF, Jones P, Rofail D. The impact of iron overload and its treatment on quality of life: results from a literature review. Health Qual Life Outcomes. 2006;4:73. 4. Bou-Fakhredin R, Bazarbachi AH, Chaya B, Sleiman J, Cappellini MD, Taher AT. Iron overload and chelation therapy in non-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Indeed, NGS revealed that 53% of 183 Mayo Clinic ET patients harbored one or more sequence variants/mutations other than JAK2/CALR/MPL, being TET2 and ASXL1 the most frequent ones. Interestingly, some of these variants are reported at high VAF in the literature, in a non-negligible fraction of cases within large cohort studies focusing on the topic of triple-negative MPNs (44) and clonal hematopoiesis of indeterminate potential (CHIP) (45,46). In accordance with these data, in our cohort we also found a high VAF, with a mean value of 43%.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, NGS revealed that 53% of 183 Mayo Clinic ET patients harbored one or more sequence variants/mutations other than JAK2/CALR/MPL, being TET2 and ASXL1 the most frequent ones. Interestingly, some of these variants are reported at high VAF in the literature, in a non-negligible fraction of cases within large cohort studies focusing on the topic of triple-negative MPNs (44) and clonal hematopoiesis of indeterminate potential (CHIP) (45,46). In accordance with these data, in our cohort we also found a high VAF, with a mean value of 43%.…”
Section: Discussionsupporting
confidence: 90%
“…9 The use of NGS is further supported by the observation that atypical JAK2 and MPL mutations have been identified in series of TN-MPN. [10][11][12] Our series prompted the histological review in cases with available material. Of 13 cases where no identifiable clonal marker was identified 4 patients showed morphological features of ET ( figure 1, table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of myeloid neoplasm-related gene derangements constitutes a major diagnostic criterion (i) to prove the clonal nature of the disease (particularly in TN cases); and/or (ii) to support/exclude specific disease subtypes [55]. With its increasing availability in the clinical setting, targeted NGS also allows the detection of atypical mutations in driver genes and of genetic derangements impacting on disease progression [56][57][58]. The quantitative assessment of VAF can also provide clinically relevant information on the disease burden and on the risk of adverse events.…”
Section: Mpn With Unconventional Molecular Featuresmentioning
confidence: 99%
“…It should also be noted that large cohort studies on TN MPNs [56] and CHIP [75,76] report high allele burdens for the above-mentioned variants in a substantial fraction of patients, implying a relevant role for such (even "high risk") imbalances in sustaining clonal hematopoiesis.…”
Section: Mpn With Chip-like Molecular Featuresmentioning
confidence: 99%